Militärgeschichtliche Zeitschrift (Oldenbourg Wissenschaftsverlag, 1967)
Published by the ZMSBw (Center for Military History and the Social Sciences Potsdam), the Journal of Military History (MGZ) is the successor journal to Military History Dispatches (MGM), which first appeared in 1967. MGZ reflects the topical breadth and methodological diversity of modern military historiography, exploring the connections between the military, culture, and society from multiple viewpoints.